Cephalic salivary glands of two species of advanced eusocial bees (Hymenoptera: Apidae): morphology and secretion - Poiani, Silvana B. [UNESP]; Cruz-Landim, Carminda da [UNESP] (Sociedade Brasileira de Zoologia, 2010)
Some adult eusocial bees have a pair of cephalic salivary glands (CSG) in addition to the thoracic labial or salivary gland pairs. This paper deals with variations in morphological features and secretion production of the CSG of females and males of Apis mellifera Linnaeus, 1758 and Scaptotrigona postica Latreille, 1807. The following life stages were studied: newly emerged, nurse, and forager workers; newly emerged and egg-laying queens; and newly emerged and sexually mature males. The histological results showed that the CSG differs between the two species in the following features: while alveoli and duct cells are cuboidal in workers and queens of A. mellifera, they change from cuboidal to flat in S. postica as the workers age. The glands of newly emerged males and females of A. mellifera are similar. However, as males become sexually mature, glands degenerate and practically disappear. The secretion from the glands of females of both species is oleaginous and gradually accumulates in the lumen of the alveoli in the beginning of the adult phase. Consequently, forager workers and egg-laying queens exhibit more turgid alveoli than younger individuals. Sudan black and Nile's blue staining indicated that the CSG secretion consists of neutral lipids. The possible role of gland secretion is discussed taking in account tasks performed by the individuals in the particular phases studied.
Keywords: Apis mellifera; histochemical; labial gland; lipid; Scaptotrigona postica